PERSEPSI MAHASISWA PRGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA TERHADAP PERKULIAHAN DARING DI MASA COVID-19 - Taufik, Taufik; Marlina, Leni; Yulianti, Eka (Jurnal Ilmiah Mandala Education (JIME), 2022)
The practice of online education is currently being intensively carried out by various levels of education starting from the elementary school level to the university level, including STKIP Yapis Dompu, there are no more learning activities in classrooms as was usually done by educators before the existence of Covid-19 pandemic outbreak. As a result, learning methods that originally relied on lectures and physical interaction have drastically changed to online. This study aims to look at the perceptions of students of the Indonesian language and literature education study program regarding the process of implementing online learning during the pandemic, such as the media used, types of communication, and student learning styles. The type of research used is descriptive qualitative research. Sources of data used are primary and secondary data sources. The primary data sources are students of the fifth semester of the Indonesian language and literature education program. Meanwhile, the secondary data are campus data. Data collection techniques used are observation, interview and documentation techniques. The results of this study indicate that the perception of Indonesian Language and Literature Education students towards online learning during the Covid-19 pandemic is less effective. These results are concluded from the research data which shows the perceptions of students who are more inclined to the weaknesses and obstacles experienced during the learning process. These obstacles include: unstable internet network, limited student cell phone memory space, lack of interaction during the online learning process and the difficulty of students understanding the delivery of material delivered by lecturers during the online learning process, so that the implementation of online learning during the Covid-19 pandemic. 19 is considered less than the maximum